Pengaruh Motivasi, Persepsi Biaya Pendidikan dan Lama Pendidikan Terhadap Minat Mahasiswa Akuntansi untuk Mengikuti Pendidikan Profesi Akuntansi (PPAk) (Studi Kasus Pada Perguruan Tinggi di Bandar Lampung) - Angrita Denziana; Resti Fitri Febriani (Universitas Bandar Lampung (UBL), 2017)
This study aims to determine whether the motivation, perception of educationcosts and the length of education affect the interest of accounting students to follow accounting profession education (PPAk). This study is an empirical study conducted with the object of research that is a student majoring in accounting at universities in the city of Bandar Lampung. Data collection was done through questionnaires. The sampling technique used is purposive sampling, with the total sample of 94 students. Data analysis in this study used data quality test, classical assumption test, and hypothesis test consisting of multiple linear regressionanalysis, F test, R2 test, and t test using SPSS.The results showed that the value of R2 obtained by 0.692, which means 69.2% interest in accounting students to follow accounting profession education (PPAk) is influenced by motivation, perception of education costs and length of education. The remaining 30.8% is influenced by other variables outside the model. The result of t test shows that the motivation, perception of education cost and the duration of education have positive and significant effect to the interest of accounting student to follow accounting profession education (PPAk).